Waste Sorting and Processing Education for Children through Game Applications that Use Loud Sound Levels - Bill Berthan Panjaitan; Erdhi Widyarto Nugroho; FX Hendra Prasetya (Journal of Business and Technology, 2022)
Garbage is one of the big problems in society.lack of awareness of throwing garbage in its place worsen the situation. Waste processing has also become more difficult because waste is not sorted. lack of knowledge of sorting waste does not make matters better. To deal with this problem, the government launched a bank sampah program to reduce waste problems. But garbage banks don't accept all types of waste. The waste bank only accepts waste that can be recycled. Therefore a game was created to teach sorting garbage and not to litter. It was made with a sound sensor to give a unique impression in the game.  The game development is designed with a reward and punishment system to tell players if they do the right thing.  After the game is finished, tests are conducted on several elementary school children and the results are that EE, PE, and HM have an influence on the BI variable.